Issues of Investment Management in Kazakhstan - Shayakhmetova K.; Orazbaeva K.; Iskakova B.; Baimamyrov B. (SHS Web of Conferences)
The article concludes that a significant increase in the efficiency of infrastructure enterprises and activation of modernization processes are possible only with the participation of the State both through mobilization of public finances and motivational factors formed by the State that encourage private investors to finance infrastructure industries. For the Republic of Kazakhstan the most attractive sources of financing industrial-innovative activity are foreign investments, financial leasing, development of the venture investment system and project financing. In order to attract potential investors to the Kazakhstan market, first and foremost it is necessary to reduce taxes and introduce incentive benefits for investments in the manufacturing sector as at present the bulk of investments belong to the extractive industry. It will give a powerful momentum of implementation of the country's investment opportunities for accelerated technological modernization and digitalization of Kazakhstan’s economy under the conditions of the Fourth Industrial Revolution and it will increase labor productivity and competitiveness of the country on the World market, ensuring an increase in the living standards of the population.